Peranan Guru Sejarah dalam Menanamkan Rasa Nasionalisme Siswa Kelas X di SMA Negeri 14 Samarinda - Ayu Indah Utami; Asnar Asnar; Jawatir Pardosi (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2017)
This research attempts to obtain information about the participation of teachers history in infuse of nationalism on student X in senior high school 14 Samarinda. The results show that participations of teachers history in imparting flavor nationalism to their students class x in senior high school 14 Samarinda is participation of teachers history in imparting flavor nationalism students are teachers as examples, teachers as inspiratory, teachers as a motivator, and teachers as an evaluator. History teacher found obstacles to imparting flavor nationalism to their students are background students is different, development of technology had an impact on thinking pattern students, the influence of the mass media, and facilities schools that had not yet fully sufficient in supporting teaching history.